Role of angiotensin II in dynamic renal blood flow autoregulation of the conscious dog - Just, Armin; Ehmke, Heimo; Wittmann, Uwe; Kirchheim, Hartmut (The journal of physiology, 2002)
The influence of angiotensin II (ANGII) on the dynamic characteristics of renal blood flow (RBF) was studied in conscious dogs by testing the response to a step increase in renal artery pressure (RAP) after a 60 s period of pressure reduction (to 50 mmHg) and by calculating the transfer function between physiological fluctuations in RAP and RBF. During the RAP reduction, renal vascular resistance (RVR) decreased and upon rapid restoration of RAP, RVR returned to baseline with a characteristic time course: within the first 10 s, RVR rose rapidly by 40 % of the initial change (first response, myogenic response). A second rise began after 20-30 s and reached baseline after an overshoot at 40 s (second response, tubuloglomerular feedback (TGF)). Between both responses, RVR rose very slowly (plateau). The transfer function had a low gain below 0.01 Hz (high autoregulatory efficiency) and two corner frequencies at 0.026 Hz (TGF) and at 0.12 Hz (myogenic response). Inhibition of angiotensin converting enzyme (ACE) lowered baseline RVR, but not the minimum RVR at the end of the RAP reduction (autoregulation-independent RVR). Both the first and second response were reduced, but the normalised level of the plateau (balance between myogenic response, TGF and possible slower mechanisms) and the transfer gain below 0.01 Hz were not affected. Infusion of ANGII after ramipril raised baseline RVR above the control condition. The first and second response and the transfer gain at both corner frequencies were slightly augmented, but the normalised level of the plateau was not affected. It is concluded that alterations of plasma ANGII within a physiological range do not modulate the relative contribution of the myogenic response to the overall short-term autoregulation of RBF. Consequently, it appears that ANGII augments not only TGF, but also the myogenic response.
Gesehen am 27.04.2021